Evaluación del componente florístico y su estructura en el remanente de bosque secundario de la finca la Lola del cantón Quevedo, provincia de los Ríos - Romero Rueda, Daniel Alexander (2022)
The present study was carried out with the purpose of knowing the diversity and structure of the forest remnant of the La Lola farm located in the Quevedo canton, province of Los Ríos. For this, three test units 20 x 50 (1000 m²) were found in an area of 6 ha, considering individuals with DBH ≥ 10 cm. A total of 110 individuals grouped into 17 species and 12 families were obtained.